Progressive symmetric erythrokeratoderma with absent mutation in LOR gene. - Puneetha, Basavanaika; Sahana, M Srinivas; Gourish, Laad (European Journal of Pediatric Dermatology, 2023)
Progressive symmetric erythrokeratoderma (PSEK) is a rare hereditary disease of keratinization, characterized clinically by symmetric erythematous and hyperkeratotic plaques and genetically inherited as an autosomal dominant trait with variable expression and incomplete penetrance. The genetic basis is unclear, although a mutation in the loricrin gene (LOR) and rarely in the connexin gene (CON) has been described. We report a case of PSEK in which genetic analysis did not highlight mutations in the LOR gene, suggesting further genetic research into the etiology of PSEK.